2010
DOI: 10.1007/s13280-010-0107-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Ethnobotanical Skills and Agricultural Labor in Forest Clearance: Evidence from the Bolivian Amazon

Abstract: Research on the benefits of local ecological knowledge for conservation lacks empirical data on the pathways through which local knowledge might affect natural resources management. We test whether ethnobotanical skills, a proxy for local ecological knowledge, are associated to the clearance of forest through their interaction with agricultural labor. We collected information from men in a society of gatherers-horticulturalist, the Tsimane' (Bolivia). Data included a baseline survey, a survey of ethnobotanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…This hypothesis is consistent with the findings of Reyes-García et al (2008), who found a positive association between the level of TEK of male household heads and crop diversity in their swidden fields. Similarly, it fits well with the results of Reyes-García et al (2011), who claimed that the more TEK Tsimane' individuals had (1) the more selective and efficient they were in clearing old-growth forest (because they practiced joint production while clearing), and (2) the less fallow forest they cleared (which suggests they lengthened the fallow because they used these forests more efficiently too). We argue that villages with higher levels of TEK may not only have more efficient cultivators and forest managers, but also more experienced foragers who can gather edible wild food in the forest, as well as more skilled hunters and fishers.…”
Section: Associations Between Tsimane' Traditional Ecological Knowledsupporting
confidence: 86%
“…This hypothesis is consistent with the findings of Reyes-García et al (2008), who found a positive association between the level of TEK of male household heads and crop diversity in their swidden fields. Similarly, it fits well with the results of Reyes-García et al (2011), who claimed that the more TEK Tsimane' individuals had (1) the more selective and efficient they were in clearing old-growth forest (because they practiced joint production while clearing), and (2) the less fallow forest they cleared (which suggests they lengthened the fallow because they used these forests more efficiently too). We argue that villages with higher levels of TEK may not only have more efficient cultivators and forest managers, but also more experienced foragers who can gather edible wild food in the forest, as well as more skilled hunters and fishers.…”
Section: Associations Between Tsimane' Traditional Ecological Knowledsupporting
confidence: 86%
“…1). The Tsimane' are one of the largest indigenous groups in the Bolivian Amazon and inhabit a densely forested area (Reyes-García et al 2010). The study area has a mean annual temperature of 25.8°C (Navarro & Maldonado 2002), and a mean annual rainfall of 1743 mm (Godoy et al 2008).…”
Section: Study Areamentioning
confidence: 99%
“…Evidences from a recent meta-analysis published by van Vliet et al [9] suggest that these swidden cultivators are mostly located in the mountainous and hilly parts of Latin America, Central Africa and Southeast Asia (SEA). Based on the Institute of Scientific Information (ISI) Web of Science database (8 October 2013), swidden agriculture is mainly practiced by smallholder farmers in a conservative estimate of 64 developing countries ( Figure 1, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]) from Africa, Latin America, and South/Southeast Asia. Forty-five of them are part of the United Nations collaborative initiative on Reducing Emissions from Deforestation and forest Degradation (or the UN-REDD Programme) partner countries (currently 48 in total).…”
Section: Introductionmentioning
confidence: 99%
“…It shows that the monitoring of swidden agriculture will greatly contribute to implementing and managing the REDD projects [10]. [9,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%